(3GdJYGed eY hSGFd GdEYdGe (B:s (3GdCSS h GdCOhGJ (B/s - (3dYjGVj,fUQ GdOjf s ((3GdTGQbI (B:s (3OGFQI GdKbGaI h GdEYdGe ,s, 2006)
(3gd JhLO VQhQI dJCcjO CgejI hSGFd GdEYdGe aj MjGJfG GdeYGUQI h GdJPcjQ HOhQgG GdfTjW h GdaYd aj JTcjd PGFbJfG GdafjI h Ubd ghGjJfG GdELJeGYjI h GdKbGaKI?h gd jhLO eGjOYh ddJfhjg HOhQgG cTQjc cGed aj JQHjI CHfGFfG h JYdjege? QHeG jYJbO GdHYV Gf gPG GdJCcjO h GdJPcjQ h GdJfhjg HeKd LgOG dG WGFd efg dCf GdMjGI GdjhejI JbOe dfG ef GdOQhS h GdJLGQH eG jcaj dEbfGY CcKQ GdeJQOOjf HOQhQ hSGFd GdZYdGe aj MjGJfG GdYGeI h GdNGUIs
Keywords: (3GdEYdGes; (3GdUMGaIs; (3JMQjQs